A new 7-diethylamino-4-hydroxycoumarin based reversible colorimetric/fluorometric probe for sequential detection of Al3+/PPi and its potential use in biodetection and bioimaging applications. (19th March 2021) - Mathivanan, Moorthy; Tharmalingam, Balamurugan; Devaraj, Thangaraj; Murugan, Abinayaselvi; Lin, Chia-Her; Jothi, Mathivanan; Murugesapandian, Balasubramanian
Abstract : A new 7 -diethylamino- 4 -hydroxycoumarin appended acylhydrazone probe was prepared and utilized for the sequential detection of Al 3+ /PPi in a reversible off–on–off emissive manner. The various practical applications of the probe were established. Abstract : Herein, we have developed a new 7 -diethylamino- 4 -hydroxycoumarin appended acylhydrazone (L ) probe using a simple condensation reaction. The structure of the probe L was characterized via single crystal X-ray analysis. This probe L can selectively detect Al 3+ metal ions via a colorimetric as well as fluorescence turn-on strategy over other metal ions. Besides, the probe can also detect the aluminium ions in pharmaceutical tablets. The resulting L-Al 3+ ensemble has been exploited as a turn-off fluorescence sensor for the detection of pyrophosphate (PPi) anion through metal displacement or by using a decomplexation approach. Based on reversible "off–on–off" emission characteristics, the probe was applied for the construction of molecular logic gates and the development of a paper strip kit for on-site detection applications. In addition, this ensemble can also be utilized to detect PPi released during DNA synthesis and biological extracts, and in live cells.